Nasopharyngeal Microbiomes in Donkeys Shedding Streptococcus equi Subspecies equi in Comparison to Healthy Donkeys - Zhu, Yiping; Chen, Shulei; Yi, Ziwen; Holyoak, Reed; Wang, Tao; Ding, Zhaoliang; Li, Jing (Frontiers in Veterinary Science, 2021)
Streptococcus equi subsp. equi (S. equi) is the pathogen causing strangles, a highly infectious disease that can affect equids including donkeys of all ages. It can persistently colonize the upper respiratory tract of animals asymptomatically for years, which serves as a source of infection. Several strangles outbreaks have been reported in the donkey industry in China in the last few years and pose a great threat to health, production, and the welfare of donkeys. Nasopharyngeal swab samples for culture and PCR are used widely in strangles diagnosis. Additionally, microbiomes within and on the body are essential to host homoeostasis and health. Therefore, the microbiome of the equid nasopharynx may provide insights into the health of the upper respiratory tract in animals. There has been no study investigating the nasopharyngeal microbiome in healthy donkeys, nor in donkeys shedding S. equi. This study aimed to compare nasopharyngeal microbiomes in healthy and carrier donkeys using 16S rRNA gene sequencing. Nasopharyngeal samples were obtained from 16 donkeys recovered from strangles (group S) and 14 healthy donkeys with no history of strangles exposure (group H). Of those sampled, 7 donkeys were determined to be carriers with positive PCR and culture results in group S. In group H, all 14 donkeys were considered free of strangles based on the history of negative exposure, negative results of PCR and culture. Samples from these 21 donkeys were used for microbial analysis. The nasopharyngeal microbiome composition was compared between the two groups. At the phylum level, relative abundance of Proteobacteria was predominantly higher in the S. equi carrier donkeys than in healthy donkeys (P < 0.01), while Firmicutes and Actinobacteria were significantly less abundant in the S. equi carrier donkeys than in healthy donkeys (P < 0.05). At the genus level, Nicoletella was detected in the upper respiratory tract of donkeys for the first time and dominated in carrier donkeys. It is suspected to suppress other normal flora of URT microbiota including Streptococcus spp., Staphylococcus spp., and Corynebacterium spp. We concluded that the nasopharyngeal microbiome in S. equi carrier donkeys still exhibited microbial dysbiosis, which might predispose them to other airway diseases.